The Moderating Role of Capital Adequacy on Bank Specific Characteristics to Sustainable Growth: Evidence From Commercial Banks in Indonesia - Restiana Ie Tjoe Linggadjaya; Apriani Dorkas Rambu Atahau; Gracia Shinta S. Ugut; Kim Sung Suk (SAGE Open, 2025)
Despite its significance, the impact of capital adequacy on sustainable growth for banks has hardly been investigated. We examine the moderating role of capital adequacy on bank-specific characteristics of sustainable growth. This quantitative study is conducted for forty-seven listed commercial banks in Indonesia from 2013 to 2022. It is the first research on the moderating role of capital adequacy on determinants of sustainable growth for banks. The results substantiate the significant adverse influence of profitability, leverage, efficiency, and liquidity on sustainable growth, while a positive influence of lagged sustainable growth and asset efficiency. Contradicting effect of capital adequacy is observed. Capital adequacy moderates profitability, leverage, liquidity, and efficiency from negative to positive, however, it moderates asset efficiency from positive to negative. The limitation is that the study is only conducted for commercial banks in Indonesia, and it does not consider the core equity and non-core equity, bank ownership, mediators, and other moderators on sustainable growth. Future research to address the limitations with a distinct study on the moderating role of capital adequacy on determinants of sustainable growth for dividend-paying banks in ASEAN countries. JEL Classification: G21, G28.